Analysis of Determinants of PCV Immunization Uptake and Pneumonia Incidence Among Under-Five Children in the Catchment Area of Sei Rampah Community Health Center - Reni Aprinawaty Sirait; Rotua Sumihar Sitorus; Yuliana (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Pneumonia remains a leading cause of morbidity and mortality among children under five, particularly in developing countries. The Pneumococcal Conjugate Vaccine (PCV) is effective in preventing Streptococcus pneumoniae infection; however, its utilization in Indonesia, including at Sei Rampah Primary Health Center, remains low. This study aimed to analyze factors influencing PCV utilization and its association with pneumonia incidence. A cross-sectional analytic design was applied to 262 mothers with children aged 0–59 months selected through simple random sampling. Data were collected using questionnaires and medical records, and analyzed using univariate, Chi-square, and logistic regression tests (p < 0.05; 95% CI). The results showed that knowledge, attitudes, and access to healthcare services were significantly associated with PCV utilization, with access being the most dominant factor (OR = 3.08; 95% CI: 1.75–5.42). Family support was significant in bivariate analysis but not in multivariate analysis. PCV utilization significantly reduced the risk of pneumonia (OR = 0.28; 95% CI: 0.13–0.60; p = 0.001). In conclusion, PCV utilization is mainly influenced by access to healthcare, knowledge, and attitudes, and has a protective effect against pneumonia. Strengthening health education and improving service access are essential to increase coverage